2021
DOI: 10.1093/botlinnean/boab028
|View full text |Cite
|
Sign up to set email alerts
|

An Indomalesian origin in the Miocene for the diphyletic New World jewel orchids (Goodyerinae, Orchidoideae): molecular dating and biogeographic analyses document non-monophyly of the Neotropical genera

Abstract: The jewel orchids (Goodyerinae), named after their often colourful leaves, have a pantropical distribution with a clear Asian centre of diversity. However, the Nearctic and Neotropical America together form a second centre of diversity, with one-third of known species of Goodyerinae. Previously, only a few American samples have been included in phylogenetic studies, and their putatively Asian origins and American divergence times were poorly known. To elucidate these topics, we inferred phylogenetic trees, per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 64 publications
1
9
0
Order By: Relevance
“…Specifically, clade A included North American species ( G. striata and G. pubescens ) and they diverged at 10.88 Mya (95% HPD = 7.86–13.63 Mya) in comparison with c . 8.4 Mya of Smidt et al ( 2021 ) ( Figure 4 ). The diversification of Goodyera mainly occurred in 14 Mya, when the temperature began to decrease, which is similar to the result of Briggs ( 1995 ).…”
Section: Discussionmentioning
confidence: 81%
See 4 more Smart Citations
“…Specifically, clade A included North American species ( G. striata and G. pubescens ) and they diverged at 10.88 Mya (95% HPD = 7.86–13.63 Mya) in comparison with c . 8.4 Mya of Smidt et al ( 2021 ) ( Figure 4 ). The diversification of Goodyera mainly occurred in 14 Mya, when the temperature began to decrease, which is similar to the result of Briggs ( 1995 ).…”
Section: Discussionmentioning
confidence: 81%
“…Erythrodes was affiliated to clade C with the characteristics of no-marking leaves and reflexed lateral sepals based on nuclear ITS, plastid trn L-F, and mat K genes (Hu et al, 2016 ). Chen et al ( 2019 ) and Smidt et al ( 2021 ) defined that clade C is the Microchilus subclade, in which diverse species exist including some Goodyera species. The results of Tu et al ( 2021 ) showed that Aspidogyne was a sister to the rest of clade C, followed by G. fumata , whereas Erythrodes and Goodyera formed a subclade based on plastid-coding genes' dataset.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations